Evaluation of Spinal Fusion in Thoracic and Thoracolumbar Spine on Standard X-Rays: A New Grading System for Spinal Interbody Fusion. Issue 7 (September 2022) - Patil, Nirmal D.; El Ghait, Hussein Abou; Boehm, Christian; Boehm, Heinrich
Study Design: Retrospective evaluation of prospectively collected data. Objective: Analyzing time course and stages of interbody fusion of a uniformly operated cohort, defining a grading system and establishing diagnosis-dependent periods of bone healing. Methods: Sequential lateral radiographs of 238 patients (313 levels) with interbody fusion operated thoracoscopically were analyzed. Results: Evaluation of 1696 radiographs with a mean follow-up of 65.19 months and average numbers of 5.42 (2-18) images per level was performed. Diagnoses were Pyogenic Spondylitis (74), Fracture (96), Ankylosing Spondylitis (38) and Degenerative Disease (105). No case with Grade 2 deteriorated to Grade 5. On average, Grade 4 persisted for 113 days, Grade 3 for 197 days, Grade 2 for 286 days and Grade 1 for 316 days. The first 95% of levels ("Green Zone", ≤ Grade 2) fused at 1 year, the remaining 4% levels fused between 12 and 17 months ("Yellow Zone") and the last 1% ("Red Zone") fused after 510 days. Conclusion: Sequential lateral radiographs permit evaluation of interbody fusion. Grade 2 is the threshold point for fusion; once accomplished, failure is unlikely. If fusion (Grade 2, 1 or 0) is not reached within 510 days, it should be regarded as failed. The 510-day-threshold could reduce the necessity of CT scanning for assessing fusion.